Effectiveness of isometric exercise in the management of tendinopathy: a systematic review and meta-analysis of randomised trials. Issue 1 (4th August 2020) - Clifford, Christopher; Challoumas, Dimitris; Paul, Lorna; Syme, Grant; Millar, Neal L
Abstract : Objective: To systematically review and critically appraise the literature on the effectiveness of isometric exercise in comparison with other treatment strategies or no treatment in tendinopathy. Design: A systematic review and meta-analysis of randomised controlled trials. Data sources: Electronic searches of Medline, Cumulative Index to Nursing and Allied Health Literature, EMBASE and Cochrane were undertaken from inception to May 2020. Methods: Overall quality of each study was determined based on a combined assessment of internal validity, external validity and precision. For each outcome measure, level of evidence was rated based on the system by van Tulder et al . Results: Ten studies were identified and included in the review, including participants with patellar (n=4), rotator cuff (n=2), lateral elbow (n=2), Achilles (n=1) and gluteal (n=1) tendinopathies. Three were of good and seven were of poor overall quality. Based on limited evidence (level 3), isometric exercise was not superior to isotonic exercise for chronic tendinopathy either immediately following treatment or in the short term (≤12 weeks) for any of the investigated outcome measures. Additionally, for acute rotator cuff tendinopathy, isometric exercise appears to be no more effective than ice therapy in the short term (limited evidence; level 3). Summary: Isometric exercise does not appear to be superior to isotonic exercise in the management of chronic tendinopathy. The response to isometric exercise is variable both within and across tendinopathy populations. Isometric exercise can be used as part of a progressive loading programme as it may be beneficial for selected individuals. PROSPERO registration number: CRD42019147179.